Childhood and adolescence : - Rathus, Spencer A. (New york University, 2006)
This work presents the facts, theories, and processes of developmental psychology in an easy-to-read style. The main points of the major theories are described, compared to other theories, their strengths and weaknesses are shown, and it is made clear when conflicts have not been resolved. The book presents the psychoanalytic, behaviouristic, cognitive-developmental, ecological, and behaviour genetic fundamentals. It then illustrates how various theoretical viewpoints, though sometimes in opposition, all bring validity to the point being made. The book is organized topically to focus intently on developmental processes and to provide students with an uninterrupted view of the sequences of change that children and adolescents experience within each developmental domain. It stresses the fundamental interplay among biological, cognitive, social, and cultural influences of each aspect of development, so students do not lose sight of the whole person and the holistic character of human development